Cerebrovascular and Endovascular Neurosurgery Complication Avoidance and Management (Springer International Publishing, 2018)
This book is an up-to-date, well-referenced practical resource that offers detailed guidance on the avoidance and management of complications in patients treated for cerebrovascular and spinal vascular disease. All complication avoidance and management techniques currently available to the endovascular/cerebrovascular surgeon are reviewed by pioneers and leaders in the field to provide the clinician with an advanced single point of reference on the subject. The book is divided into four sections. It opens by discussing general issues, such as definition of complications, medicolegal aspects, the role of resident training, and checklists. The subsequent three sections address the avoidance and management of complicatio ns when performing surgical, endovascular, and radiosurgical procedures, covering the full range of indications and potential adverse events. All chapters have a standardized format, simplifying the search for information on a specific disease process. Numerous intraoperative images are included, and, when appropriate, algorithms for the avoidance, early recognition, and management of complications are presented. Each chapter concludes with a checklist of preparatory steps and "emergency procedures" that each member of the team must perform in order to ensure the best possible outcomes.